2019
DOI: 10.1002/hon.2601
|View full text |Cite
|
Sign up to set email alerts
|

Transformed follicular lymphoma in the rituximab era: A report from the Spanish Lymphoma Oncology Group

Abstract: Follicular lymphoma (FL) is the second most common non‐Hodgkin lymphoma (NHL) subtype. The histological transformation (HT) of FL is an event considered frequent in the natural history of this tumor. We studied the transformation rates, predictive factors, and treatment characteristics that may impact in the survival of patients with FL and HT. A total of 1074 patients diagnosed with FL were prospectively enrolled from 1990 to 2016 in a Spanish registry. Sixty‐four HTs were recorded based on clinical criteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Our data show no transformation due to, in our opinion, the small sample size and the retrospective nature of the study, and not because an absence of suspicion or the performance of fewer biopsies than indicated, since in the data collection, biopsies at relapse were specified, all with negative results. As previously published, our group has proven experience in lymphoma transformation 14 Prospective and larger sample size trials are needed to know the real rate of transformation.…”
Section: Discussionmentioning
confidence: 91%
“…Our data show no transformation due to, in our opinion, the small sample size and the retrospective nature of the study, and not because an absence of suspicion or the performance of fewer biopsies than indicated, since in the data collection, biopsies at relapse were specified, all with negative results. As previously published, our group has proven experience in lymphoma transformation 14 Prospective and larger sample size trials are needed to know the real rate of transformation.…”
Section: Discussionmentioning
confidence: 91%
“…Prior anthracycline chemotherapy for indolent FL is associated with poor post-transformation survival of 21% [5]. Patients who receive prior non-anthracycline chemotherapy for indolent FL and subsequently transform have inferior 5-year OS compared to chemotherapy-naive patients in retrospective studies (53% vs 93%, p < 0.01) [31]. FL that transformed within 2 years of prior BR had a 2-year OS of 40% [32].…”
Section: Discussionmentioning
confidence: 99%
“…16 A Spanish registry series reported that 5-year OS for patients treated with chemotherapy before HT was 55% (95% confidence interval, 38%-69%) vs 81% (95% confidence interval, 53%-93%; P = .009) for those who had not received prior chemotherapy. 17 The poor prognosis for patients with prior chemoimmunotherapy may be independent of prior anthracycline exposure; for example, patients with HT after prior bendamustine, rituximab (BR) have a 2-year OS of only 40%. 9 In this Canadian report, the authors reported that the main driver of POD24 was occult or early transformation.…”
Section: Initial Approach For Patients With Tfl Who Have Received Prior Chemoimmunotherapymentioning
confidence: 99%